Acceleration of Early Strength Development in Mortars Containing Soluble Silica Extracted from Palm Oil Clinker - Ismail, A.H.; Kusbiantoro, A.; Muthusamy, K.; Mortar, N.A.M. (2024)
Soluble silica from palm oil clinker was extracted using Laine’s method. It involved two major steps, namely water reflux and distillation. The use of 480 g of POCP and 12 hours of distillation in the extraction experiment resulted in 53.50% of dissolved silica, which was the highest gain among the trial experiments and was chosen as an optimum parameter for the subsequent characterisation analysis. In addition, its effect on cement hydration was studied by including it as a filler in mortar mixtures. Mortar with 7.50% of extracted silica gained high strength in the early days of curing and performed well throughout the maturing age. The rapid hardening properties of soluble silica-based mortar would promote the potential of soluble silica as an additive for rapid hardening.